2020
DOI: 10.1002/ijgo.13198
|View full text |Cite
|
Sign up to set email alerts
|

Maternal health and non‐communicable disease prevention: An investment case for the post COVID‐19 world and need for better health economic data

Abstract: An integrated approach to population health, disease surveillance, and preventive care will dominate the health agenda in the post COVID-19 world. Because of their huge burden and the vulnerability imposed during a health crisis, prevention and care of non-communicable diseases (NCDs) will need to be prioritized even further. Maternal and child health are inextricably linked with NCDs and their risk factors. The intergenerational impact of poor maternal nutrition and health conditions during pregnancy, particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 66 publications
(92 reference statements)
0
21
0
1
Order By: Relevance
“…Currently, the United States also has the highest number of COVID‐19 infections worldwide 107 . In light of the global COVID‐19 pandemic, there has been a call for renewed prioritization of non‐communicable diseases such as obesity that increase susceptibility of women with SARS‐CoV‐2 infection to severe disease or mortality 108 . Carefully designed epidemiologic studies are required to assess the linkage between COVID‐19 disease severity, obesity, and associated socioeconomic factors.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the United States also has the highest number of COVID‐19 infections worldwide 107 . In light of the global COVID‐19 pandemic, there has been a call for renewed prioritization of non‐communicable diseases such as obesity that increase susceptibility of women with SARS‐CoV‐2 infection to severe disease or mortality 108 . Carefully designed epidemiologic studies are required to assess the linkage between COVID‐19 disease severity, obesity, and associated socioeconomic factors.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of chronic degenerative diseases is related to an increased risk of complications and death from COVID-19 [ 18 ], including in Mexico [ 19 ]. However, as other authors indicated previously [ 20 ], the impact of these highly prevalent diseases on the clinical evolution of COVID-19 in pregnant women has not been analyzed. We found that DM and chronic kidney disease are risk factors for death among patients of childbearing age with a positive test, but were not found as risk factors for mortality among pregnant patients with or without a positive test.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 crisis has called for a reimagination of places, people, and strategies for healthcare organizations to prepare for the postpandemic phase ( 11 , 12 , 13 ). In this recovery process, we learned important lessons of effective, tailored communications, cross disciplinary teamwork, and innovative solutions.…”
Section: Discussionmentioning
confidence: 99%